Difficulties arising from marriage crisis with international elements: commentary to SAP Zaragoza (Second Section) of 16 November 2018 - Sánchez Cano, María Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The Sentence of the Provincial Court of Zaragoza hears an appeal of a divorce that presents international elements and that allows the so called conflict of civilizations to shine through, while it raises the problems raised by the unilateral Islamic repudiation. This institution is not contemplated in our positive Law and may even be contrary to the Spanish international public policy. In addition, the resolution resolves other questions that are equally interesting from the perspective of Private International Law, such as the amount fixed as maintenance in favour of the minor child of the marriage and the attribution of the use of the family home to the minor and his mother.